(untitled) (Research, Society and Development, 2026)
This paper analyzes the informational crisis in water resource management in Brazil, using the São Francisco River Transposition Project (PISF) as a case study. The analysis is based on the theoretical framework of Luciano Floridi’s Information Ethics, employing concepts such as "Infosfera," "informational entropy," and the ethical duty of transparency. It is argued that the physical and operational failures of the PISF are a direct reflection of a systemic failure in informational governance, characterized by a lack of institutional transparency and the active dissemination of disinformation. The objective was to understand how informational entropy undermines social trust and compromises environmental justice. The concepts of Infosphere, ontocentric ethics, and informational entropy are adopted as tools for critical analysis of the Brazilian water situation, with an emphasis on the municipality of Petrolina, Pernambuco, a region heavily dependent on irrigation from the São Francisco RiverThis process generates a state of entropy that erodes public trust, paralyzes qualified debate, and compromises sustainable decision-making. The study concludes by proposing principles for an informationally ethical water governance, highlighting transparency as a fundamental condition for water security and democratic stability in the country.